SOLUSI TERHADAP PROBLEM PERCAYA DIRI (SELF CONFIDANCE) - Alkhofiyah, Mufydatush Sholihah (STAINU Purworejo, 2021)
Individuals who have self-confidence feel confident in their abilities, so they can solve their problems because they know what is needed in their life, and have a positive attitude based on their beliefs and abilities. The individual is responsible for the decisions that have been made and looks at facts and reality objectively based on skills. But in reality, there are still individuals who do not have self-confidence in themselves or their abilities. Many individuals tend to feel hopeless and have no motivation to live this life. Many individuals have very low self-confidence In this article, the authors collect data by identifying thoughts or findings contained in books, papers, journals or articles related to the topic. Discussions using descriptive methods to explain the main ideas related to the topic of discussion. The results of this study include a person's self-confidence is influenced by two factors, namely internal factors and external factors. Internal factors that come in individuals that affect the individual in him such as self-concept, self-esteem, physical conditions, and life experiences. While external factors that come from outside such as education, work, and the environment as well as life experiences.